2005
DOI: 10.1258/0023677054307042
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in haematology and serum chemistry of Weiser–Maples guineapigs (Cavia porcellus)

Abstract: SummaryAge-related changes in haematology and serum chemistry values were examined in male and female Weiser-Maples guineapigs (Cavia porcellus). Haematological changes that significantly (Po0.01) correlated with ageing were increased white blood cell and neutrophil counts in both sexes, decreased lymphocyte counts in both sexes, decreased reticulocyte and platelet counts in males, and decreased basophil counts in females. For serum chemistry, increases in total protein, triglycerides, blood urea nitrogen and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
31
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 21 publications
(22 reference statements)
12
31
1
2
Order By: Relevance
“…The age-related reduction in the production of PCEs observed in our study is similar to that in rat (Kojima et al, 1999) and guineapigs (Kitagaki et al, 2005), in which the young animals showed the highest values of PCE in peripheral blood, suggesting an age-related decrease in hematopoiesis. The age-related reduction in the production of PCEs observed in our study is similar to that in rat (Kojima et al, 1999) and guineapigs (Kitagaki et al, 2005), in which the young animals showed the highest values of PCE in peripheral blood, suggesting an age-related decrease in hematopoiesis.…”
Section: Discussionsupporting
confidence: 85%
“…The age-related reduction in the production of PCEs observed in our study is similar to that in rat (Kojima et al, 1999) and guineapigs (Kitagaki et al, 2005), in which the young animals showed the highest values of PCE in peripheral blood, suggesting an age-related decrease in hematopoiesis. The age-related reduction in the production of PCEs observed in our study is similar to that in rat (Kojima et al, 1999) and guineapigs (Kitagaki et al, 2005), in which the young animals showed the highest values of PCE in peripheral blood, suggesting an age-related decrease in hematopoiesis.…”
Section: Discussionsupporting
confidence: 85%
“…A general increase of total protein and globulin levels with increasing age has been reported in other species, including hystricomorph rodents (Kaneko 1997, Kitagaki and others 2005). …”
Section: Discussionsupporting
confidence: 52%
“…The ALP enzyme was found to decrease with body weight, as in other species (Clifford and White, 1999). Levels of ALP are reported to decrease sharply after birth and then level off in male and female guinea pigs of the inbred Weiser-Maples strain (Kitagaki et al, 2005).…”
Section: Alkaline Phosphatase (Alp)mentioning
confidence: 99%